Subjective Comparison Between Dyop and Snellen Refractions. - Sanni, Isiaka Oluwasegun; Odjimogho, Efe Sunny (Optometry & Visual Performance, 2020)
Background: A Dyop (or dynamic optotype) is a spinning visual target which uses the strobic detection of the spinning gaps/segments of the ring to measure visual acuity. Methods: Forty subjects with visual acuity better than 6/12 (20/40) and ages between 20 and 28 years (24.48 ± 2.01 years) were recruited at the University of Benin Optometry Clinic. Snellen and Dyop acuity charts were displayed on a monitor at a distance of 6 meters. The assessment sequence between the two acuity chart formats was alternated for every other patient to reduce potential refractionist bias. Subjective refraction was measured in both eyes, and the duration of testing for each patient and each method was recorded. Results: There was no significant mean Thibos notations difference, M (p = 0.77), J0 (p = 0.27), and J45 (p = 0.57) using the Bland-Altman plot and 95% limits of agreement between the two charts, and there were no differences as to age or gender. There was, however, a disparity in the mean acuity of about 0.25 diopters with the mean Snellen acuity of 1.60 ± 0.21 decimal units and the mean Dyop acuity of 1.17 ± 0.14 decimal units with a linear relationship: y = 0.3121x + 0.6709 (p = 0.00). The refraction with a Dyop acuity chart also typically took half as long (339 ± 122 seconds) as the refraction with a Snellen acuity chart (680 ± 281 seconds), p = 0.00. Conclusions: Subjective refractions with a Dyop chart were comparable to a Snellen chart. The efficiency of a Dyop refraction, however, was typically twice that of the Snellen chart, with a narrower variance in visual acuity measurements and an improved level of acuity of about 0.25 diopters.